Multinational Union Activity in the Paper Industry - Northrup, Herbert; Rowan, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
After considering the many attempts of cooperation among unions in multinational firms particularly the paper industry, the authors are not optimistic about results in the immediate future.